Stability of ¤-derivations on Lie C¤-algebras - Kim, Soo Hwan; Kim, Ga Ya; Kim, Seong Sik (JOURNAL OF ADVANCES IN PHYSICS, 2014)
In this paper, we investigate the stability and superstability problems for ¤-derivations associated with the generalized Jensen type functional equation on Lie C¤-algebras.